The Modified Imitation Game: A Method for Measuring Interactional Expertise - Arsal, Güler; Suss, Joel; Ward, Paul; Ta, Vivian; Ringer, Ryan; Eccles, David W. (Frontiers in Psychology, 2021)
The study of the sociology of scientific knowledge distinguishes between contributory and interactional experts. Contributory experts have practical expertise—they can ‘walk the walk.’ Interactional experts have internalized the tacit components of expertise—they can ‘talk the talk’ but are not able to reliably ‘walk the walk.’ Interactional expertise permits effective communication between contributory experts and others (e.g., laypeople), which in turn facilitates working jointly toward shared goals. Interactional expertise is attained through long-term immersion into the expert community in question. To assess interactional expertise, researchers developed the imitation game—a variant of the Turing test—to test whether a person, or a particular group, possesses interactional expertise of another. The imitation game, which has been used mainly in sociology to study the social nature of knowledge, may also be a useful tool for researchers who focus on cognitive aspects of expertise. In this paper, we introduce a modified version of the imitation game and apply it to examine interactional expertise in the context of blindness. Specifically, we examined blind and sighted individuals’ ability to imitate each other in a street-crossing scenario. In Phase I, blind and sighted individuals provided verbal reports of their thought processes associated with crossing a street—once while imitating the other group (i.e., as a pretender) and once responding genuinely (i.e., as a non-pretender). In Phase II, transcriptions of the reports were judged as either genuine or imitated responses by a different set of blind and sighted participants, who also provided the reasoning for their decisions. The judges comprised blind individuals, sighted orientation-and-mobility specialists, and sighted individuals with infrequent socialization with blind individuals. Decision data were analyzed using probit mixed models for signal-detection-theory indices. Reasoning data were analyzed using natural-language-processing techniques. The results revealed evidence that interactional expertise (i.e., relevant tacit knowledge) can be acquired by immersion in the group that possesses and produces the expert knowledge. The modified imitation game can be a useful research tool for measuring interactional expertise within a community of practice and evaluating practitioners’ understanding of true experts.